Gain modulation of the middle latency cutaneous reflex in patients with chronic joint instability after ankle sprain - Futatsubashi, Genki; Sasada, Shusaku; Tazoe, Toshiki; Komiyama, Tomoyoshi (Clinical neurophysiology, 2013)
•We investigated the modulation of cutaneous reflexes in the lower limb muscles of subjects with ankle sprain and joint instability.•The cutaneous afferent pathway was modified in the subjects with chronic ankle instability after ankle sprain.•These new findings partly shed light on the problem of impaired ankle joint regulation in patients with chronic ankle instability. To investigate the neural alteration of reflex pathways arising from cutaneous afferents in patients with chronic ankle instability. Cutaneous reflexes were elicited by applying non-noxious electrical stimulation to the sural nerve of subjects with chronic ankle instability (n=17) and control subjects (n=17) while sitting. Electromyographic (EMG) signals were recorded from each ankle and thigh muscle. The middle latency response (MLR; latency: 70–120ms) component was analyzed. In the peroneus longus (PL) and vastus lateralis (VL) muscles, linear regression analyses between the magnitude of the inhibitory MLR and background EMG activity showed that, compared to the uninjured side and the control subjects, the gain of the suppressive MLR was increased in the injured side. This was also confirmed by the pooled data for both groups. The degree of MLR alteration was significantly correlated to that of chronic ankle instability in the PL. The excitability of middle latency cutaneous reflexes in the PL and VL is modulated in subjects with chronic ankle instability. Cutaneous reflexes may be potential tools to investigate the pathological state of the neural system that controls the lower limbs in subjects with chronic ankle instability.